Youth Participation in Digital Democracy: A Narrative Analysis of Global Civic Engagement Reports - Deo Renaldi Saputra; Khodijah Asshofiah; Fu'ad Sholikhi (Anthroposia: Journal of Social and Human Development, 2026)
The expansion of digital communication infrastructures has transformed democratic participation, positioning youth as central actors in emerging forms of networked civic engagement while simultaneously subjecting their participation to institutional framing and governance narratives. Despite growing scholarly attention to digital citizenship and online activism, limited research has examined how global civic engagement reports construct and legitimize youth participation through narrative structures that shape policy expectations and democratic imaginaries. This study employs a non-empirical qualitative design based on interpretive document analysis and narrative policy analysis, examining transnational civic engagement reports published between 2015 and 2025. Through multi-stage coding that combines narrative structuring, thematic interpretation, and cross-document comparison, the study identifies recurring storylines that position youth as innovators, governance partners, and symbols of democratic renewal, while also revealing narratives of fragility, risk, and institutional control. The findings indicate that global reports function not only as descriptive accounts but also as discursive mechanisms that define the normative boundaries of legitimate participation and influence how digital democracy is conceptualized and operationalized. The study concludes that understanding youth participation in digital democracy requires attention to narrative framing processes that shape democratic meaning, policy priorities, and future institutional expectations, thereby highlighting the analytical importance of narrative approaches in contemporary democracy research.